A critical evaluation and refinement of the performance prediction of wet-cooling towers - Kloppers, Johannes Christiaan (Stellenbosch : University of Stellenbosch, 2008)
Thesis (PhD (Mechanical and Mechatronic Engineering))--University of Stellenbosch, 2003.